Managing tourism emissions through optimizing the tourism demand mix: Concept and analysis. (December 2020) - Sun, Ya-Yen; Lin, Pei-Chun; Higham, James
Abstract: Carbon mitigation strategies are an urgent and overdue tourism industry imperative. The tourism response to climate action has been to engage businesses in technology adoption, and to encourage more sustainable visitor behaviour. These strategies however are insufficient to mitigate the soaring carbon footprint of tourism. Building upon the concepts of optimization and eco-efficiency, we put forward a novel carbon mitigation approach, which seeks to pro-actively determine, foster, and develop a long-term tourist market portfolio. This can be achieved through intervening and reconfiguring the demand mix with the fundamental aim of promoting low carbon travel markets. The concept and the analytical framework that quantitatively inform optimization of the desired market mix are presented. Combining the "de-growth" and "optimization" strategies, it is demonstrated that in the case study of Taiwan, great potential exists to reduce emissions and sustain economic yields. The implications for tourism destination managers and wider industry stakeholders are discussed. Highlights: Optimizing the demand mix to promote low carbon travellers has a great potential for carbon mitigation. A methodological and analytical framework is presented to inform optimization of the desired market mix. Combining the "de-growth" and "optimization" strategies is an efficient approach to reduce CO2 and sustain economic yields. Destinations are encouraged to pro-actively determine, foster, and develop a long-term tourist market portfolio.